Choumiryou Tradisional Pada Masakan Jepang Modern - Sri Wahyu Istana Trahutami (KIRYOKU, 2019)
This article discusses how Japanese people use traditional herbs in Japanese cuisine. Traditional spices or choumiryou which are the focus of research are limited to basic spices consisting of miso, shoyu, and dashi produced from konbu and katsuobushi. Data is collected through documentation of articles and books relating to traditional Japanese spices. The purpose of writing is to find out the type and method of making choumiryo that characterizes Japanese cuisine, as well as how the basic ingredients are used in a dish. The method used is descriptive qualitative to get a complete type and process of making the basic seasoning. From the analysis results it is known that the basic seasoning in Japanese cuisine is not derived from spices as used in Southeast Asian cuisine. Most of Choumiryo comes from the fermentation process of soybeans, beans, wheat or rice, and comes from fish. The manufacturing process is also complex and takes months. Through this process, a delicious taste is produced as well as a natural food preservative.